Weight restoration in patients with anorexia nervosa after stereotactic surgery and brain morphometric insights - Fengting Wang; Wei Liu; Halimureti Paerhati; Zhengyu Lin; Kuanghao Ye; Lulin Dai; Tao Wang; Zhaohui Lan; Dianyou Li; Yijie Lai; Bomin Sun; Shikun Zhan (BMC Psychiatry)
Abstract Background Bilateral anterior capsulotomy and deep brain stimulation (DBS) of the nucleus accumbens (NAc) represent investigational treatment options for severe, treatment-refractory anorexia nervosa (AN). However, follow-up studies evaluating postoperative outcomes in these patients remain limited, and the clinical and neuroanatomical characteristics associated with treatment response have yet to be elucidated. Methods The retrospective study analyzed the preoperative imaging data of AN patients who underwent bilateral anterior capsulotomy or nucleus accumbens (NAc) DBS from 2019 to 2023. Voxel-based morphometry (VBM) was employed to assess structural differences between AN patients and healthy controls (HCs), as well as to identify brain regions associated with postoperative changes in body mass index (BMI). Results Nineteen patients were included in the analysis, six of whom received NAc DBS. The mean (standard deviation, SD) BMI of patients significantly increased from 13.4 (2.5) kg/m² preoperatively to 20.7 (5.3) kg/m² postoperatively (t = 5.45, p < 0.001). A significant smaller gray matter volume was observed in widespread regions in AN patients compared to HCs including the cerebellum, the thalamus, the temporal, orbital frontal gyrus and the sensorimotor gyrus in VBM analysis (PFWE < 0.001, cluster size > 30 voxels). After controlling for age, sex, surgical type, and total intracranial volume (TIV), no clusters passed the correction for multiple comparisons in the correlational analysis with BMI changes after surgeries. The volume of the left caudate and the right middle frontal gyrus showed a positive correlation with the percentage of BMI changes, while the volume of the right supplementary motor area, the right parahippocampal gyrus, the right precuneus, and the left cerebellum exhibited a negative correlation in peak-level analysis (Puncorrected < 0.001). Conclusions Both ablative and DBS surgeries demonstrate efficacy in promoting weight restoration in severe AN patients. The structural integrity of specific brain regions may play a role in predicting postoperative BMI recovery. Further studies with a larger number of patients are warranted to better evaluate the outcome of the surgeries and the predictive value of the imaging characteristics.